Planos de ensino e formação continuada de professores: o curso de comunicação social da Universidade Cidade De São Paulo - Souza, Ricardo Felix de (2008)
The greatest challenge higher education institutions have been facing nowadays is to educate increasingly autonomous and critical students by having them build their own global knowledge, as well as students who are able to help improving their social environment. In order to try to cope with such challenge, institutions have now been organizing their courses in more flexible curricula, according to professional demands. This new criterion requires teachers and professors to deeply examine their teaching and to seek for continuous improvement, which should bring them enough knowledge for planning their lessons in accordance with consistent learning.The paper herein presented intends to critically analyze the development of Teaching Plans drawn up for the Social Communication course and its academic qualifications for Publicity and Advertising offered by Universidade Cidade de São Paulo – UNICID, due to the fact that such Plans do not follow the policy described in the Pedagogic Project designed for the course, which seriously compromises the course quality. This paper also discusses the Teaching Plan as a document whose propositions go far beyond a lesson planner, as it is indeed an essential means for developing the identity of higher education courses.